Faktor Pengaruh Keputusan Pengguna Jasa Kapal PELNI Semarang Di Masa Pandemi - Gembong Satria Negara; Iwan Weda (STEKOM PRESS, 2022)
In 2019 PT.PELNI (Persero) with ships to and from Semarang experienced an increase in passengers. The need for companies to continue to innovate through aspects of the company in terms of comfort, service, and brand image to balance the costs or prices incurred by service users. One of the strategies carried out by PT PELNI (Persero) is to make a number of ship service adjustments amid the Covid-19 outbreak. One of them is preparing a policy to apply the portstay scheme in turn for all ships.This research uses data collection methods in the form of observations made directly in the field, literature study, and documentation and questionnaire methods. In this study, the authors used qualitative and quantitative data analysis, where the statistics found in the study were described or described as they are, then presented in the form of numbers which were then represented in a description.It shows that, based on empirical data (the results of filling out the questionnaire) and the results of multiple linear regressions, it shows that the convenience variable (X1) has a positive effect on the attractiveness of service users, where the value of tcount 2.781> ttable 1.984. Service variable (X2) has a positive influence on the attractiveness of service users where the value of tcount is 3.328> t table is 1.984. Variable Brand Image (X3) also has a positive influence on the attractiveness of service users has a tcount of 2.813> t table of 1.984. Thus the results of this study indicate that there is a positive and significant influence between Comfort, Service and Brand Image on Service User Interest.